Multi-Ethnic and Hinduism in Afghanistan (Universitas Islam Negeri Imam Bonjol Padang, 2021)
Although the Taliban group is well known, it is not the only representation of ethnic and religious groups in Afghanistan. Besides being inhabited by various groups from internal Islam, there are also Hindus and Sikhs. This paper aims to describe the condition of ethno-religious diversity in Afghanistan, especially regarding Hinduism. We write this article by conducting a literature study that emphasizes descriptive analysis after comparing sources from previous writings. This is obtained based on literature study with descriptive and qualitative methods. From the literature review and previous experience received from the Taliban firsthand, during the Taliban rule from 1996 to late 2001, Hindus are forced to wear yellow armbands in public to identify themselves as non-Muslims. Hindus are forced to wear the burqa, which allegedly